Optical Microscopy as a Tool for Assessing Parenteral Nutrition Solution Stability: A Proof of Concept - Luis Otero-Millán; Brais Bea-Mascato; Jose Luis Legido Soto; María Carmen Martín de la Cruz; Noemi Martínez-; Natividad Lago-Rivero (MDPI AG, 2024)
Background/Objectives: Parenteral nutrition (PN) is used when enteral feeding is not possible. It is a complex mixture of nutrients that must meet a patient's needs but can face stability issues, such as lipid emulsion destabilisation and precipitate formation. Stability studies are complex, and the methodologies used are very varied in the literature. In addition, many studies are outdated and use outdated components. This study conducts a stability analysis of PN solutions using optical microscopy. Methods: Samples were prepared according to clinical practice standards and previous studies. We used a counting chamber for optical microscopic observations and different storage conditions (RT, 4 °C 1-14 days). Results: Precipitates larger than 5 µm were found in 8 out of 14 samples after 14 days of storage at room temperature, and none were observed in refrigerated samples. More lipid globules larger than 5 µm were detected in samples stored at room temperature than in those stored in a refrigerator after 14 days. Additionally, the number of large globules generally increased from day 1 to day 14 in most samples. Conclusions: The observed precipitates were probably calcium oxalate crystals, the formation of which is possible in PN but is not expected under the usual storage conditions in a hospital environment. Prolonged storage time and storage at room temperature increases the formation of these precipitates. These findings highlight the importance of using filters during both the preparation and administration of PN to prevent large particles from reaching patients.